Exploring Business Ethics Study in Social Entrepreneurship to Foster Sustainable Green Resource Innovation: A Literature Review - Ahmad Sholihudin; Iriani Ismail (Edumaspul: Jurnal Pendidikan, 2023)
This research aims to examine the business ethics associated with sustainable green resource innovation in the context of social entrepreneurship. Secondary data was obtained from existing literature on sciencedirect.com from the last 10 years. A descriptive approach was used to describe the phenomenon, with a focus on business ethics and green resource innovation. This article discusses the concepts of social entrepreneurship and sustainable entrepreneurship, and the importance of technology to support green innovation. Business ethics in the context of social entrepreneurship, collaboration, responsibility, and green resource innovation are the focus of discussion in this article. Business ethics in social entrepreneurship is essential to foster sustainable green resource innovation. Green innovation is increasingly important in business due to increasing business interest in sustainability and customer awareness of environmental issues.